2016
DOI: 10.3354/dao02943
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects and gene expression changes in larval zebrafish after exposure to ZnCl2 and ZnO nanoparticles

Abstract: Engineered nanoparticles (NPs) can potentially generate adverse effects at the tissue, organ, cellular, subcellular, DNA, and protein levels due to their unique physico-chemical properties. Dissoluble NPs (e.g. nZnO) can be toxic in aquatic organisms. We compared effects of nZnO and corresponding concentrations of released Zn(II) by water-soluble ZnCl 2 on larval zebrafish Danio rerio (72 h post fertilization) by analyzing changes in expression levels of stressrelated genes ( p53, rad51, mt2) by qRT-PCR. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The United States Environmental Protection Agency (USEPA) established a system as an initial screen that applied zebrafish as a model for rapid identification of chemical toxicity to evaluate the effects from myriad chemical pollutants [ 38 ]. However, the biological effects of ZnCl 2 on neurobehavioral development in a vertebrate model are not well characterized in research ( Table A1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The United States Environmental Protection Agency (USEPA) established a system as an initial screen that applied zebrafish as a model for rapid identification of chemical toxicity to evaluate the effects from myriad chemical pollutants [ 38 ]. However, the biological effects of ZnCl 2 on neurobehavioral development in a vertebrate model are not well characterized in research ( Table A1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that CdS-maltodextrin QDs are able to induce cytotoxicity and cell death, alter cell proliferation and induce the production of radical oxygen species (ROS) in a dose-dependent manner [14]. QD-induced perturbations of cellular mechanisms may cause different pathophysiological processes depending on concentration and duration of exposure [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…To determine LC 50 values of CuSO 4 and Cu-NPs, stock solutions were added to each 400 mL and 2 L exposure beakers at eight different nominal concentrations (0, 40, 80, 160, 300, 600, 1200, and 3000 mg/L) for Cu 2þ and six different nominal concentrations (0, 40, 200, 500, 1000, and 3000 mg/L) for Cu-NPs, respectively, and for each experiment at least three beakers were included without Cu 2þ and Cu-NPs as an experimental control. Thirty larval zebrafish (72 hpf) were put in each beaker and tried to determine the mortality of larvae (LC 50 ) at 96 h period of time at different concentrations (Boran and Ulutas, 2016). After determination of lethal and sublethal concentration of Cu 2þ and Cu-NPs, gene expression experiments were conducted to compare Cu 2þ and Cu-NPs.…”
Section: Experimental Animals and Exposure Solutionsmentioning
confidence: 99%
“…cDNA was synthesized in the following conditions: annealing at 25 C, extending at 42 C, and heat-inactivating transcriptase at 70 C (GeneAmp ® PCR System, 9700, Applied Biosystems, California, USA). cDNA was stored at À80 C until quantitative RT-PCR (qRT-PCR) transcriptional analysis (Boran and Ulutas, 2016).…”
Section: Transcriptional Analysesmentioning
confidence: 99%